College Students' Intentions to Use Calorie Information on a Restaurant Menu: Application of the Theory of Planned Behavior. Issue 4 (3rd July 2016) - Stran, Kimberly A.; Knol, Linda L.; Severt, Kimberly; Lawrence, Jeannine C.
Abstract : Background: Obesity continues to be an epidemic in the United States and is associated with multiple chronic diseases. Greater numbers of people eat in restaurants and select high calorie foods. Labeling laws require calorie information on menus in some restaurants.Purpose: The purpose of this study was to determine the predictors of intention to use calorie labels among college students using constructs of the Theory of Planned Behavior (TPB).Methods: College students selected a meal from a menu without calories and from the same menu with calorie information, and completed a survey that addressed TPB constructs. Regression analysis was used to determine predictors of intention to use labels and calorie changes of meals ordered.Results: Students ( n  = 100) ordered significantly fewer calories with posted calorie information. Intention was significantly correlated with attitudes, subjective norms, and perceived behavioral control.Discussion: The TPB may help explain factors involved in the intention to use posted calorie information on a restaurant menu. Results support the inclusion of the calorie statements on these menus.Translation to Health Education Practice: Education efforts should include constructs of the TPB. When planning, implementing and evaluating programs, utilizing strategies to influence attitudes, subjective norms and perceived behavioral control is suggested.